The Evolution and Current Focus of Ministry with Catholics with Disabilities Within the United States - Baum, Michelle N. (Journal of religion, disability & health, 2006)
The authors provide an historical overview of outreach to Catholics with disabilities within the U.S., including the contributions of early pioneers in the ministry. They also describe the founding of the National Catholic Partnership on Disability and its current activities and future directions, as well as the work of numerous Catholic ministry partners.